Novel treatments in optic pathway gliomas - Maheshwari, Akash; Pakravan, Mohammad; Charoenkijkajorn, Chaow; Beres, Shannon J.; Lee, Andrew G. (Frontiers in Ophthalmology, 2022)
Optic pathway gliomas (OPG) are primary tumors of the optic nerve, chiasm, and/or tract that can be associated with neurofibromatosis type 1 (NF1). OPG generally have a benign histopathology, but a variable clinical course. Observation is generally recommended at initial diagnosis if vision is stable or normal for age, however, treatment may include chemotherapy, radiotherapy, or surgery in select cases. This manuscript reviews the literature on OPG with an emphasis on recent developments in treatment.